Enterprise Architecture and Services in Cloud Computing: A Survey - Sajjan, RS; Yashwantrao, Biradar Rekha; Harshal, Torvi (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing provides services such as software, platform, storage, applications, network, etc, over the Internet based on a pay-as-you-use approach. Cloud computing is a business model or key tool in the IT world. Organizations experience increasing pressure to change or move organization to respond continuously in changing environment. Enterprise Architecture can be used to solve this challenge. With cloud services and deployment models, the organizations can upgrade their existing Information Technology provision. Enterprise Architecture is a layered architecture which helps not only to build Information Technology models but also makes the organization up to date. Enterprise Architecture describes the process for an organization to achieve short-term and long-term goals. Enterprises incorporating appropriate Enterprise Architecture can upgrade their architectures by integrating the existing infrastructure with the Platform as a Service and Infrastructure as a Service support. They can extend 4-dimensions of Enterprise Architecture such as, data, business, application and technology architecture by utilizing the Platform as a Service and Software as a Service. Thus, Cloud Computing can provide a foundation to build new Enterprise Architecture for organization, on demand with cost effective manner.